Deciphering structural bases of intestinal and hepatic selectivity in targeting pregnane X receptor with indole-based microbial mimics - Li, Hao; Illés, Peter; Karunaratne, Chamini V; Nordstrøm, Lars Ulrik; Luo, Xiaoping; Yang, Annie; Qiu, Yunping; Kurland, Irwin J; Lukin, Dana J; Chen, Weijie; Jiskrová, Eva; Krasulová, Kristýna; et al. (Bioorganic chemistry, 2021)
Microbial metabolite mimicry is a new concept that promises to deliver compounds that have minimal liabilities and enhanced therapeutic effects in a host. In a previous publication, we have shown that microbial metabolites of L-tryptophan, indoles, when chemically altered, yielded potent anti-inflammatory pregnane X Receptor (PXR)-targeting lead compounds, FKK5 and FKK6, targeting intestinal inflammation. Our aim in this study was to further define structure-activity relationships between indole analogs and PXR, we removed the phenyl-sulfonyl group or replaced the pyridyl residue with imidazolopyridyl of FKK6. Our results showed that while removal of the phenyl-sulfonyl group from FKK6 (now called CVK003) shifts agonist activity away from PXR towards the aryl hydrocarbon receptor (AhR), the imidazolopyridyl addition preserves PXR activity in vitro. However, when these compounds are administered to mice, that unlike the parent molecule, FKK6, they exhibit poor induction of PXR target genes in the intestines and the liver. These data suggest that modifications of FKK6 specifically in the pyridyl moiety can result in compounds with weak PXR activity in vivo. These observations are a significant step forward for understanding the structure-activity relationships (SAR) between indole mimics and receptors, PXR and AhR.
Keywords: hepatocyty; racionální návrh léčiv; střeva; Male; vztahy mezi strukturou a aktivitou; Models, Molecular; indoly; lidé středního věku; Drug Design; Animals; pregnanový X receptor; Intestines; konformace proteinů; Humans; Adenocarcinoma; Mice; Molecular Structure; Intestinal inflammation; Middle Aged; molekulární struktura; Anti-Inflammatory Agents; mužské pohlaví; Female; antiflogistika; molekulární mimikry; Hepatocytes; Microbial mimics; ženské pohlaví; Liver; Cell Line, Tumor; nádorové buněčné linie; zvířata; Indoles; Colonic Neoplasms; Molecular Mimicry; nádory tračníku; adenokarcinom; Pregnane X Receptor; Tryptophan catabolites; lidé; molekulární modely; játra; Pregnane X receptor; Structure-Activity Relationship; Protein Conformation; myši